Questioning the Banality of Evil / Alex Haslam and Steve Reicher Reassess the Evidence - Sutton Jon; The British Psychological Society (2008)
Looking Back, When Therapy Causes Harm, Nostalgia, Capability ans Resilience, Psychology in Assertive Outreach.